CONTRIBUTION OF HEIGHT, WEIGHT, THIGH CIRCUMFERENCE AND LEG LENGTH TO THE FOOTBALL PLAYING SKILLS OF REAL MADRID ACEH SOCIAL SPORT SCHOOL STUDENTS - Maulana, Darkani (Universitas Syiah Kuala, 2024)
The ability to play soccer is influenced by psychological factors and physiological factors. physiological factors, namely physical organs in which height, weight, thigh circumference and leg length. This study aims to determine the height, weight, thigh circumference and leg length contribution to the soccer playing skills of Real Madrid Aceh Social Sports School Students. The population of this study were all athletes of Real Madrid Aceh Social Sports School Students. The results of data analysis can be obtained from the average height of 165, body weight 55.047, thigh circumference 50.5238, the correlation coefficient of leg length (X1) with soccer playing skills (Y) of 0.77, with r count r table (0.77 0.433) so that there is a contribution between X1 and Y. Height, weight, thigh circumference there is a contribution of leg length with soccer playing skills of Real Madrid Aceh Social Sports School Students.Keywords: Anthropomertics, Skills, Playing Football